Structure and registry of the silica bilayer film on Ru(0001) as viewed by LEED and DFT. Issue 48 (1st December 2022) - Soares, Edmar A.; Paier, Joachim; Gura, Leonard; Burson, Kristen; Ryczek, Catherine; Yang, Zechao; Stavale, Fernando; Heyde, Markus; Freund, Hans-Joachim
Abstract : Structure and registry of the silica bilayer film with respect to its supporting metal substrate revealed by low energy electron diffraction. Abstract : Silica bilayers are stable on various metal substrates, including Ru(0001) that is used for the present study. In a systematic attempt to elucidate the detailed structure of the silica bilayer film and its registry to the metal substrate, we performed a low energy electron diffraction (I/V-LEED) study. The experimental work is accompanied by detailed calculations on the stability, orientation and dynamic properties of the bilayer at room temperature. It was determined, that the film shows a certain structural diversity within the unit cell of the metal substrate, which depends on the oxygen content at the metal-bilayer interface. In connection with the experimental I/V-LEED study, it became apparent, that a high-quality structure determination is only possible if several structural motifs are taken into account by superimposing bilayer structures with varying registry to the oxygen covered substrate. This result is conceptually in line with the recently observed statistical registry in layered 2D-compound materials.